Impact of the Chilean military dictatorship on social workers in the Provident Funds: a look at our social welfare (1960-1990) - Román-Guajardo, Karin Andrea; Araya-Cuello, Marlene Rosa (Prospectiva. Revista de Trabajo Social e Intervención Social, 2025)
This article reviews a variety of statesmen from social workers and other officials belonging to the area of social welfare in Chile, during the transition from the system of Provident Funds to the establishment of the AFP individual capitalization system (Administrator of the Pension Fund) during the 1980s in the context of the military dictatorship. The main objective is to understand the impact that this key event has on the profession of social work and social security profession in Chile up to the present.